Analisis Kinerja Sistem Informasi Ekspedisi Nasional Berorientasi Website dan Mobile - Puti Indah Balqis A; Agus Munandar (Universitas Sains dan Teknologi Komputer, 2026)
This study aims to evaluate the performance of digital information systems, including websites and mobile applications, used by national expedition companies in Indonesia, using standardized technical indicators from Google Web.dev. This research employs a descriptive and evaluative approach with purposive sampling. The research objects comprise five major national expedition companies: JNE, J&T Express, SiCepat, Pos Indonesia, and Lion Parcel. The evaluation is conducted using four main indicators: Performance, Accessibility, Best Practices, and Search Engine Optimization (SEO). The results indicate that, in general, the digital information systems of national expedition companies function adequately; however, there are notable performance variations among companies, particularly in terms of loading speed and mobile performance. Pos Indonesia demonstrates the most balanced overall performance, while several other companies require further optimization, especially in performance efficiency and SEO. This study contributes to the literature by providing an objective technical evaluation of expedition information systems and offering practical recommendations to improve digital service quality, enabling faster, more secure, and more responsive logistics services in a highly competitive industry.